Fairy tail. 14 - Mashima, Hiro, 1977- (Kodansha Comics, 2011)
"Laxus wants Fairy Tail for himself, and he's set his three powerful allies against the entire guild! But when the attacks of Laxus's right-hand man become sadistic, the guild's angel, Mirajane, is forced to reveal the frightening satanic power she's been hiding for so long!"--P. [4] of cover.